SINTESIS DAN KAREKTERISASI SENYAWA KIRAL HASIL REAKSI ANTARA METILEUGENOL KASAR DENGAN ASAM ASETAT - Muh. Hajir S. Lasapo; Erwin Abdul Rahim; Ruslan Ruslan; Indriani Indriani (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
The research about synthesis and characterization of chiral compounds from the rough methyleugenol with acetic acid as the catalyst has been done. The goal is to determine the content of 1-(3,4-dimetoksifenil)-2-propanil acetate compound which is produced in the reaction process of metileugenol with acetic acid and to characterizased the chemical compound of the product. The results showed that the content of 1-(3,4-dimetoksifenil)-2-propanil acetate compound that has been obtained was 45.87% with a molecular weight of 238.Keywords : Methyleugenol, Chiral, FT-IR, GC-MS